Optimization-Based Sizing of Battery-Fuel Cell Hybrid Propulsion Systems for Hydrogen-Powered High-Speed Trains - Temiz, Mehmet Sami; Boynuegri, Ali Rifat; Yigit, Hayri (MDPI, 2026)
The decarbonization of railway transportation requires energy-efficient propulsion technologies capable of reducing fossil fuel dependence and improving the operational efficiency of rail systems. Hydrogen fuel cell (FC)-battery hybrid powertrains have emerged as a promising alternative for non-electrified high-speed railway lines due to their potential for energy-efficient operation and reduced environmental impact. However, the optimal sizing and coordinated operation of these hybrid energy sources remain a challenging problem because energy efficiency, component degradation, and system cost are strongly interrelated. This study proposes a degradation-aware mixed-integer linear programming (MILP) framework for the optimal sizing and energy management of a FC-battery hybrid propulsion system for high-speed trains. The optimization simultaneously determines the capacities of FC stacks, battery modules, and hydrogen storage while minimizing the overall lifecycle cost and improving system energy utilization. Battery and FC degradation models are incorporated into the optimization problem through linearized formulations to ensure realistic long-term operation. The proposed framework is evaluated using real operational data in the approximately 71 min high-speed rail corridor between Bursa and Osmaneli in T & uuml;rkiye. Simulation results show that increasing battery capacity significantly reduces FC stress while enabling more efficient energy utilization through regenerative braking and power balancing. The results indicate that optimal battery sizing can notably improve system performance, reducing the total lifecycle cost from 1.12 & times;109 USD to 5.65 & times;108 USD, while decreasing the required number of fuel cell units from 31 to 18 and mitigating fuel cell degradation. The proposed approach provides an effective design tool for energy-efficient hydrogen-powered railway systems.
Keywords: hydrogen trains; fuel cell-battery hybrid systems; mixed-integer linear programming (MILP); energy-efficient railway systems; Computer Science; Engineering; Physics